Resolution of Giant Coronary Aneurisms in a Child With Refractory Kawasaki Disease Treated With Anakinra - Gambacorta, Alessandro; Buonsenso, Danilo; De Rosa, Gabriella; Lazzareschi, Ilaria; Gatto, Antonio; Brancato, Federica; Pata, Davide; Valentini, Piero (Frontiers in Pediatrics, 2020)
Kawasaki disease is an acute, self-limited febrile illness of unknown cause that predominantly affects children < 5 years of age. IVIG, the standard treatment, have reduced coronary involvement to <5%. Patients who are resistant to initial IVIG are at an increased risk of developing coronary arteries aneurysms and its optimal treatment remains controversial. We present a case of intravenous immunoglobulin, steroids and infliximab-resistant Kawasaki Disease in a 9-month-old child, which developed giant aneurysms, successfully treated with anakinra, a recombinant antagonist of the IL-1 receptor. In our case the introduction of IL-1 Receptor Antagonist therapy seems to have blocked the disease both from a clinical and laboratory point of view. We also noted a very rapid regression of coronary aneurysms passed from giant aneurysms to small ones, or, as in the case of the anterior descending artery, the complete disappearance of the aneurysm formation. We think that our case add more evidences to the potential role of IL-1RA as therapy in some selected cases of refractory KD, in particular with severe involvement of coronary arteries, although new efficacy trials are needed to clarify the role of Anakinra in these patients.